META-ANALISIS PENERAPAN METODE BERMAIN PERAN TERHADAP KETERAMPILAN BERBICARA SISWA SEKOLAH DASAR - Siti Hanifa Ari Utami; Haryadi Haryadi (Universitas Muria Kudus, 2022)
The purpose of this study is to re-analyze the application of the role playing method to the speaking skills of elementary school students.The research method used is meta-analysis by summarizing various research results by examining the parts of each study and the relationship between each study to obtain in-depth conclusions on the research studied with a sample of 10 national journals that are relevant to the title of the research conducted. The data collection technique was carried out by searching electronic journals through Google Scholar with the keywords